Bio-indigo Production using Wild-type Acinetobacter sp. and Indole-3-acetate Monooxygenase (iacA) Expressed in Escherichia coli - Ahn, Sooyeon; Park, Seo A.; Kumar, Pradeep; Choi, Kwon Young (Biotechnology and Bioprocess Engineering, 2023)
This study reports the identification of a novel bio-indigo-producing bacterium from soil sources. Blue-colored colonies were first screened and isolated from a screening plate containing M9 minimal medium and 1.0 mM indole. The blue colony was selected among various colonies and identified as an Acinetobacter species. The purified blue dye exhibited a distinct spectral feature of λmax at 490 nm. The structure of the dye was then analyzed. Thin-layer chromatography separation and liquid chromatography/mass spectrometry analysis confirmed that the blue dye was indigo (with Rf and m/z values of 0.8 and 263.4, respectively). Wild-type Acinetobacter sp. could produce bio-indigo up to 1.018 ± 0.013 mg/L in an M9 minimal medium supplemented with 1.0 mM indole. Next, the genes involved in the production of indigo were investigated using sequence analysis and by comparing them with those in related Acinetobacter species. The indole-3-acetate monooxygenase-encoding gene iacA was found to be responsible for indigo synthesis from indole. The iacA gene was then amplified and expressed in Escherichia coli BL21(DE3), and the recombinant E. coli strain could produce bio-indigo at levels up to 0.291 ± 0.027 g/L over 24 h. Indigo production was highly dependent on indole substrate feeding. These findings may facilitate the industrial bioprocess of bio-indigo production.
Keywords: Acinetobacter sp; Acinetobacters; Bio-indigo dye; Iacum; Indigo dye; Indole; Indole-3-acetate monooxygenase; Minimal medias; Monooxygenases; Wild types; Acinetobacter sp; bio-indigo dye; IacA; indole; indole-3-acetate monooxygenase